Preliminary study on effect of hydrothermal temperature during TiO2 synthesis on the biodiesel production from waste cooking oil - Nurashina Abdul Rahman; Anita Ramli; Chong, Fai Kait (Penerbit Universiti Kebangsaan Malaysia, 2021)
In the present work, effect of hydrothermal temperature from 120 to 160 °C on TiO2 physicochemical properties as well as its photocatalytic activity towards biodiesel production using waste cooking oil (WCO) was investigated. TiO2 was synthesized via hydrothermal method using Titanium butoxide, Ti(OBu)4 as the precursor and nitric acid, HNO3 as the peptizing agent. Next, the synthesized photocatalyst was dried at 60 °C for 24 h and later calcined at 400 °C for 2 h. The synthesized TiO2 was characterized using X-ray diffraction (XRD) and Burnauer- Emmet- Teller (BET) to determine their crystallinity and textural properties. Results showed that all synthesized TiO2 have a mixture of anatase and rutile phase and N2 adsorption- desorption isotherm for all catalyst possess Type IV isotherm according to IUPAC classification with hysteresis loop of type H1. Then, all the synthesized catalysts were tested for biodiesel production using esterified waste cooking oil under visible light irradiation for 1 h and 10 min. Percentage of fatty acid methyl ester (FAMEs) present in the synthesized biodiesel was determined using gas chromatography with flame ionization detector (GC-FID). The synthesized catalyst (T24_160) showed a good photocatalytic activity as the percentage of biodiesel yield was higher (3.41%) compared to the other catalyst.